Sexual and gender-based violence against refugee women: a hidden aspect of the refugee "crisis" - Freedman, Jane (Reproductive health matters, 2016)
The current refugee “crisis” in Europe has created multiple forms of vulnerability and insecurity for refugee women including various forms of sexual and gender-based violence. Increasing numbers of women, either alone or with family, are attempting to reach Europe to seek protection from conflict and violence in their countries, but these women are subject to violence during their journey and/or on arrival in a destination country. The lack of adequate accommodation or reception facilities for refugees and migrants in Europe, as well as the closure of borders which has increased the need for smugglers to help them reach Europe, acts to exacerbate the violence and insecurity. La « crise » actuelle des réfugiés en Europe a créé de multiples formes de vulnérabilité et d’insécurité pour les réfugiées, notamment plusieurs formes de violence sexuelle et sexiste. Les femmes, seules ou avec leur famille, sont de plus en plus nombreuses à tenter de parvenir en Europe pour y chercher protection, mais elles sont soumises à la violence pendant le voyage et/ou à l’arrivée dans un pays de destination. Le manque de logements adéquats ou d’installations d’accueil pour les réfugiés et les migrants en Europe, ainsi que la fermeture des frontières qui a augmenté la nécessité d’avoir recours à des passeurs pour atteindre l’Europe, exacerbent la violence et l’insécurité. La “crisis” actual de refugiados en Europa ha creado múltiples formas de vulnerabilidad e inseguridad para mujeres refugiadas, incluidas diversas formas de violencia sexual y de género. Crecientes números de mujeres, solas o con familia, están intentando llegar a Europa para buscar protección pero estas mujeres son sujetas a violencia durante su viaje y/o al llegar al país de destino. La violencia e inseguridad son exacerbadas por la falta de instalaciones adecuadas para alojar o recibir a refugiados y migrantes en Europa, así como el cierre de fronteras que ha incrementado la necesidad de las refugiadas de recurrir a contrabandistas para que las ayuden a llegar a Europa.